LIDERAZGO Y COMPORTAMIENTO HUMANO DE LOS TRABAJADORES DE LA EMPRESA FLEISCHMANN DE LA CIUDAD DE LOJA. - Rengel Jimenez, Gretty Elizabeth (2021)
The present thesis work was carried out in order to investigate the “Leadership and human behavior of the workers of the Fleischmann company in the city of Loja”. The general objective of this project is to determine the leadership and human behavior of the workers of the Fleischmann company in the city of Loja. Among the specific objectives, it was proposed to carry out a bibliographic review about the variables, determine the type of leadership in the company under study and propose a profile of leadership and human behavior for the workers. In the results, it was determined that the manager's leadership score emanated from the test applied to the workers was 3.96 points on the Likert scale, while in the human behavior test it was 4.34 points, the result obtained from the manager's perception of the business. Based on these results, it was determined that the leadership practiced by the manager of the company is the rational democratic style, and the human behavior of the workers is based on the continuous practice of values. Finally, the proper conclusions and recommendations resulting from the research carried out and based on the objectives set were raised.